2018
DOI: 10.1080/09243453.2018.1504801
|View full text |Cite
|
Sign up to set email alerts
|

Putting all students in one basket does not produce equality: gender-specific effects of curricular intensification in upper secondary school

Abstract: In recent decades, several countries have made an effort to increase the enrollment rates and performance of students in science and mathematics by means of mandatory, rigorous course work, which is often referred to as curricular intensification (CI). However, there is a lack of research on intended and unintended effects of CI reforms on achievement and motivation. Using representative data from the National Educational Panel Study, we examined effects of a prototypical CI reform in 1 German state. We compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 59 publications
1
13
0
Order By: Relevance
“…On the basis of these data, which were assessed in upper secondary school, we could not consider variables from lower secondary school, which might have helped us identify potential selection effects. However, in line with previous research that used these COMPARING APPLES AND ORANGES data, we found no considerable differences in observed background variables between the student cohorts (Hübner et al, 2017;Hübner et al, 2018).…”
Section: Limitations and Future Prospectssupporting
confidence: 92%
See 1 more Smart Citation
“…On the basis of these data, which were assessed in upper secondary school, we could not consider variables from lower secondary school, which might have helped us identify potential selection effects. However, in line with previous research that used these COMPARING APPLES AND ORANGES data, we found no considerable differences in observed background variables between the student cohorts (Hübner et al, 2017;Hübner et al, 2018).…”
Section: Limitations and Future Prospectssupporting
confidence: 92%
“…PB_C = p-value for the difference between the correlations in basic and advanced courses. Hübner, Wagner, Nagengast, and Trautwein (2018), we decided to exclude the specific group of basic course students in English after the reform because only a few students with a different language as the core subject chose English as a basic course after the reform. Compared with Trautwein et al (2010), we considered data only from general upper secondary schools.…”
Section: Limitations and Future Prospectsmentioning
confidence: 99%
“…Our study comes with several implications for educational practice. Detracking school reforms are often conducted in STEM subjects (science, technology, engineering, and mathematics; Domina & Saldana, 2012;Hübner et al, 2019), which are believed to be of specific importance to individuals as well as society (OECD, 2010). Detracking in STEM areas is often conducted with the aim of homogenizing student achievement in those specific subjects and consequently providing equal career chances for all students.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, gender equality can contribute to economic growth (Altuzarra et al, 2021;Santos Silva and Klasen, 2021), particularly through increased participation in STEM jobs (Maceira, 2017;Hammond et al, 2020), which critically depend on achievement, self-concept, and course choices of STEM subjects in school (Updegraff et al, 1996;Parker et al, 2012;Watt et al, 2012Watt et al, , 2017Schoon and Eccles, 2014. Referring to these arguments which underscore the relevance of monitoring effects of educational initiatives and reforms on gender disparities in general, it seems reasonable to believe that the G8-reform might specifically affect gender disparities in STEM. As girls and boys report different levels of self-concept and interest in math-intensive domains of STEM, which are central for subsequent achievement (e.g., Else-Quest et al, 2010;Hübner et al, 2017bHübner et al, , 2019Eccles and Wigfield, 2020;Wu et al, 2021), it is important to investigate if the reform-induced intensifications/compression in lower secondary school might affect gender disparities in STEM-related achievement and motivation.…”
Section: Gender and School Timementioning
confidence: 99%
“…Referring to these arguments which underscore the relevance of monitoring effects of educational initiatives and reforms on gender disparities in general, it seems reasonable to believe that the G8-reform might specifically affect gender disparities in STEM. As girls and boys report different levels of self-concept and interest in math-intensive domains of STEM, which are central for subsequent achievement (e.g., Else-Quest et al, 2010 ; Hübner et al, 2017b , 2019 ; Eccles and Wigfield, 2020 ; Wu et al, 2021 ), it is important to investigate if the reform-induced intensifications/compression in lower secondary school might affect gender disparities in STEM-related achievement and motivation.…”
Section: Gender and School Timementioning
confidence: 99%